2021
DOI: 10.1111/njb.03154
|View full text |Cite
|
Sign up to set email alerts
|

Henckelia connata (Gesneriaceae), a new species from eastern Himalayas, China

Abstract: According to morphological observation and literature consultation, a new species of Henckelia (Gesneriaceae), H. connata X. Z. Shi & Li H. Yang, is described and illustrated. This new species resembles H. dimidiata, but differs in its dilated and connate petiole bases (versus separated), longer peduncles (4-10 cm long versus 0.3-2.2 cm long) and pedicels (1.5-4.0 cm long versus up to 1 cm long), lanceolate to triangular bracts (versus ovate), of smaller size (4-7 × 3-5 mm versus up to 16 × 13 mm), bluish purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…is a member of the family Gesneriaceae. It presently includes about 75 species (GRC, 2022; Nampy et al, 2021; Shi & Yang, 2021; Shi et al, 2021; Taram et al, 2021). The genus is distributed in India, Bangladesh, Nepal, Bhutan, China, Myanmar, Sri Lanka, Thailand, Laos and Vietnam (Kanthraj et al, 2020; Taram et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is a member of the family Gesneriaceae. It presently includes about 75 species (GRC, 2022; Nampy et al, 2021; Shi & Yang, 2021; Shi et al, 2021; Taram et al, 2021). The genus is distributed in India, Bangladesh, Nepal, Bhutan, China, Myanmar, Sri Lanka, Thailand, Laos and Vietnam (Kanthraj et al, 2020; Taram et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In India, the genus is so far represented by 36 species (GRC, 2022; Taram et al, 2021), 22 of them are found occurring in the North East India and the Himalayas (Borah et al, 2019; Kanthraj et al, 2020; Krishna & Lakshminarasimhan, 2018; Nampy et al, 2021; Taram et al, 2021). After recircumscription of the genus Henckelia (Weber et al, 2011), more than 17 species have been described (Shi & Yang, 2021). The Henckelia species of North East India along with the species found in Sri Lanka were formerly attributed to Chirita sect.…”
Section: Introductionmentioning
confidence: 99%